Preferencje w zakupach młodych konsumentów w supermarketach (na podstawie własnych badań empirycznych) - Wrzesińska, Joanna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2006)
The article presents survey results dedicated to shopping habits of young consuments and their attitude to supermarkets activity in 2003 in Poland. Young consuments aged between 18 and 35 years old have positive attitude to supermarket shopping. They like possibility to buy several articles in just one place. Majority claim that supermarkets had influence on modernization of Polish market. Half of them state that they should be open on Sundays and holidays. As negative aspects of shopping in supermarkets they mention buying many useless articles, spending big amounts of money and consuming time in long waiting lines. Some researched people claimed that large shops affected nearby smaller shops and caused their bankruptcy